ANALYSIS OF DEAD CORE FORMATION IN CATALYTIC REACTION AND DIFUSION PROCESSES WITH GENERALIZED DIFUSION FUX - Skrzypacz, Piotr; Kabduali, Bek; Kadyrbek, Alua; Szafert, Sławomir; Andreev, Vsevolod; Golman, Boris (Scientific Reports, 2022)
Dead-core and non-dead-core solutions to the nonlinear diffusion–reaction equation based on the generalized diffusion flux with gradient-dependent diffusivity and the power-law reaction kinetics in catalyst slabs are established. The formation of dead zones where the reactant concentration vanishes is characterized by the critical Thiele modulus that is derived as a function of reaction order and diffusion exponent in the generalized diffusion flux. The effects of reaction order and diffusion exponent on the reactant concentration distribution in the slab and dead-zone length are analyzed. It is particularly demonstrated that by contrast to the model based on the standard Fick’s diffusion, dead-core solutions exist in the case of first-order reactions. Also, the relationship between critical Thiele moduli for models based on the generalized and standard Fick’s diffusion fluxes is established.
Keywords: Type of access: Open Access; dead-core solutions; non-dead-core solutions